2020
DOI: 10.26452/ijrps.v11ispl1.2702
|View full text |Cite
|
Sign up to set email alerts
|

Floating countries and corona pandemic: Impact of COVID-19 on stranded Cruise ships

Abstract: Cruise ships transport a significant number of people in confined spaces over an extended period than other modes of transportation, thereby presenting a unique environment to elevate human-to-human transmitted infections. The overcrowded public rooms, congested accommodations, standard food supplies, and shared sanitary facilities encourage the transmission of infectious diseases by affected persons and through contaminated food, water and surfaces. A novel coronavirus (COVID-19) originating from Wuhan, China… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…[19][20][21][22][23]. Few more related studies on impact of Covid-19 were reported [24][25][26][27].…”
Section: Resuming Life After Covid 19 Lockdownmentioning
confidence: 99%
“…[19][20][21][22][23]. Few more related studies on impact of Covid-19 were reported [24][25][26][27].…”
Section: Resuming Life After Covid 19 Lockdownmentioning
confidence: 99%